Climate of submontane location Stará Lesná (1988–2013) - BIČÁROVÁ, Svetlana; MAČUTEK, Jozef; BILČÍK, Dušan (Contributions to Geophysics and Geodesy, 2014)
This paper focuses on evaluation of climatic data obtained at MeteorologicalObservatory GPI SAS Stará Lesná according to the classical daily observations carriedout for period 1988-2013. Location is situated at the foothills of the High Tatra Mts. andrepresents submontane climate zone favourable for temperate coniferous and mixed forestvegetation. According to observations climate of Star´a Lesn´a is characterized by averageannual air temperature 5.9 °C that seasonally varies from –3.5 °C (DJF) to 15.2 °C (JJA).Air-temperature extremes range between –26.5 and 34.2 °C. Daily air temperature maximaand derived indices such as the number of summer days indicate moderate warmingduring last decade. Growing season length is about 195 days. Average annual precipitationis 744 mm, seasonal comparison shows nearly twice more precipitation amountin summer than winter half year. Snow depth is 35 cm on average, extraordinary over50 cm. Relative air humidity is about 78%. Wet periods lasted from 5 to 13 consecutivewet days; substantially longer are dry periods from 14 to 39 days. Average sunshineduration is 1806 hours per year. The number of sunny days is clearly lower than thenumber of cloudy days. Surface air pressure 920.4 hPa relates to altitudinal position ofsite. Wind blows mostly from the more open southern side. Although average wind speedis rather low (2.1 m/s), occurrence of strong wind gusts above 40 m/s can cause such aspatial destruction of natural environment as in November 2004.